Critical Theory and Dialectics of Contemporary Economics - Maialeh, Robin; Chytil, Zdeněk, 1949-; Pavlík, Ján, 1956-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
The subject of this dissertation thesis is a confrontation of contemporary economic thought with critical theory. Based on the holistic critique of the production process, the author deals with elementary principles of wealth creation and allocation, mirroring themselves in the issue of economic inequality. An applied transdisciplinary approach leads to dialectical understanding of market mechanism which accentuates an antagonistic character of its actors´ aims and reveals its non-empirical causalities. These abstract connections then become a viable explanatory complement to already advanced empirical apparatus of economic inequality. The goal of the thesis is to formulate an economic model that takes into consideration both empirical findings of contemporary studies on economic inequality and reflection of the critical theory. The value added lies in the fact that the economic model presents an interaction of economic agents and through probabilistic drive towards deepening economic inequalities exposes market mechanism as the diverging factor of social reproduction. Further, the model shows that Pareto-optimization, a frequently used analytically-normative tool of contemporary economics, principally does not suffice in grasping market-based inequalities. The contribution of the thesis is researching particular economic phenomena from the unique perspective which has not been yet fully accomplished in the context of modern economics.
Vedoucí práce: Zdeněk Chytil
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations